Offshore Financial Centers : Report on the Assessment Program and Proposal for Integration with the Financial Sector Assessment Program. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This supplement reviews the data received thus far and the progress made by participating jurisdictions in their dissemination efforts. Data for major jurisdictions that declined to participate are also provided where it is available from published sources. In addition, data on a sample of advanced economies are provided for comparative purposes. The framework identified a minimum set of variables for dissemination and recommended that jurisdictions publish data on those variables although jurisdictions could choose to publish more. Tables 2 and 5 to 13 provide the data received on those variables. The framework also identified additional variables that were to be provided to the Fund to help Fund staff monitor developments in financial centers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet